Physical and chemical modifications of tragacanth gum to improve electrospinnability for wound dressings - Zahra Nazemi; Mehdi Jalili Ahmadabad; Marjan Bahraminasab; Samaneh Arab; Mahsa Janmohammadi; Mohammad Sadegh Nourbakhsh (Carbohydrate Polymer Technologies and Applications)
Electrospun nanofibers based on tragacanth gum (TG) represent a promising candidate for wound healing applications. However, the electrospinning of this natural gum has encountered several challenges due to the colloidal nature of its aqueous solution, high viscosity, and the presence of inter- and intramolecular hydrogen bonding. To address these challenges, TG was modified through physical treatments, including ultrasonication, separation of water-soluble and water-swellable fractions via centrifugation, and dissolution in sodium chloride aqueous solution. Additionally, chemical modification through de-esterification was employed for a more thorough evaluation of the related challenges. These modifications improved the solubility of TG and reduced hydrogen bonding, thereby facilitating fiber formation compared to unmodified TG. Among the various modifications evaluated, de-esterification resulted in the most advantageous morphology, yielding uniform nanofibers with a significantly reduced diameter. Consequently, higher concentrations of de-esterified TG (3 %, and 5 % w/v) were electrospun with polyvinyl alcohol (PVA, 8 % w/v) as a carrier polymer in a 60:40 vol ratio of PVA to TG. The resulting nanofibers exhibited moderate antibacterial activity, enhanced cell viability (exceeding 100 %), improved cell adhesion, and significant scratch healing ability (around 40 %). In conclusion, electrospun nanofibers derived from chemically modified TG appear to be a promising candidate for wound healing applications.